Kaulinan Barudak sebagai Sumber Penciptaan Tari Anak-anak di Kabupaten Sumedang - Mulyati, Eti; Hendriyana, Husen (PANGGUNG, 2013)
ABSTRACTÂ This article is the result of the children dance creation which is adopted from childrenâs play culture (Kaulinan Barudak) in Sumedang community. The purpose of the research is to design dance choreography of Elementary School children which requires creativity, interpretation, and trans- formation of the artist. In the process of its creation method, the interpretation contains elements of relations, so that the sense and the meaning of the dance forms will be established. Meanwhile, the transformation demands intelligence of analysis through the established structure to be relevant and constructive. Both of these aspects are still in the realm of ideas that should be realized in the form of movement representation and composition of a dance. Dance composition can be applied both individually and in-group. Focuses on the dancer as a form of dance medium, both individually and in-group, in a unity of dance composition sourced from Kaulinan Barudak, can be assessed through the shape, composition, and function of the movement so that it reflects cultural identity and national character of the dance itself.Â Keywords:Â  kaulinan barudak, creation, children danceÂ Â ABSTRAKÂ Artikel ini merupakan hasil penelitian tentang penciptaan tari anak yang diangkat dari budaya bermain anak-anak (kaulinan barudak) masyarakat Sumedang. Tujuan penelitian ini ialah untuk merancang koreografi tari anak-anak tingkat Sekolah Dasar yang menuntut kreativitas, interpretasi, dan transformasi senimannya. Dalam proses metode penciptaan- nya, interpretasi memuat unsur-unsur relasi sehingga terbangunnya suatu makna dan arti dari bentuk tari itu sendiri, sedangkan transformasi menuntut kecerdasan analisis melalui strukstur yang dibangun sehingga relevan dan konstruktif. Kedua aspek ini masih pada ranah ide-gagasan yang perlu diwujudkan dalam bentuk representasi gerak dan kompo- sisi sebuah tarian. Komposisi gerak tari dapat diaplikasikan secara perseorangan ataupun perkelompok. Berfokus pada penari sebagai medium bentuk gerak tari, baik perseorangan maupun perkelompok dalam satu kesatuan komposisi gerak tarian yang bersumber dari kaulinan barudak, dapat dikaji melalui reka bentuk, komposisi dan fungsi bentuk gerak sehingga tergambarnya identitas kultural dan karakter bangsa dari Â bentuk tarian itu sen- diri.Â Kata kunci:Â  kaulinan karudak, penciptaan, tari anak